PENGEMBANGAN MODUL AKIDAH AKHLAK DENGAN PENDEKATAN SAINTIFIK UNTUK SISWA MIN - Nurhasanah, Nurhasanah (State Institute for Islamic Studies Batusangkar, 2019)
The background of this study is that the learning steps in the module are not yet in accordance with the scientific approach, in the module there are no activities that can motivate students to learn actively and the module components have not been clearly described. The goal to be achieved is to produce a learning module that is valid and practical, so that it can be used by teachers and students in schools, as a guide in the learning process. This type of research is development research, which is a process used to develop and validate educational products. The model used is a 4-D model that is stage (define, design, develop and disseminate). This research only reaches the practicality and stage of develop. The data analysis technique uses the Miles and Huberman model for needs analysis, and uses a formula modified by Riduwan for validity and practicality. The results of the study show that the validity of the Akidah Akhlak module with the scientific approach obtained an average of 89% with a very valid category, namely its validity. The practical test results from the implementation of the Akidah Akhlak module with the scientific approach obtained an average of 92% with very practical categories (easy to use and understood by teachers and students). Based on the explanation above, it can be concluded that the Akidah Akhlak module with the scientific approach developed can be declared very valid and very practical so that it is feasible to be used by all Akidah Akhlak subjects in school.